Optimization of Solid Oxide Cells and Stacks for Reversible Operation. (10th July 2019) - Ploner, Alexandra; Hauch, Anne; Pylypko, Sergii; Di Iorio, Stéphane; Cubizolles, Géraud; Mougin, Julie
Abstract : Solid oxide cells are among the best candidates for viable energy conversion and storage solutions. Their capability to operate reversibly as electrolyser ('SOEC mode') or as fuel cell ('SOFC mode'), provides an opportunity to balance out electricity needs. Yet, reversible operation requires an optimized cell and stack design to withstand alternating conditions. In this study, more than ten different cells have been produced and their initial performance evaluated. For selected cells, durability tests were conducted and showed that primarily the oxygen electrode contributes to performance losses in SOFC mode whereas the fuel electrode is mainly affected under SOEC mode conditions. The stack design was optimized in order to withstand the envisaged operating conditions. An optimization of internal pressure drop (reduced by a factor of 2) and sealing resistances towards higher pressure has been achieved while maintaining the electrochemical performance.